The impact of open access on the medical literature - Turk, Nana (Zdravniški vestnik, 2016)
Background: The aim of the article is to conduct an overview of the impact of OA on the medical articles based on 3-part categorization. Methods: Data were identified by a search strategy with eight combinations of keywords (open ac- cess, citation impact, citation advantage, citation count, article download, article usage, social media attention, altmetrics) and searched in three different databases. Results: The analysis was conducted on 107 studies dealing with citations, downloads and social impact. Sixty-seven of them simply employed the counting citations to OA and non-OA articles; nineteen articles compared the downloads and citations counts; and twenty-one articles investigated the social impact of OA articles. Twenty-five articles investigated the citations, download counts, and social impact of medical articles. Conclusions: The studies investigating the citation impact mostly showed citation advantages. Those that employed citation and download counts of medical articles using randomized controlled trials showed that OA articles were downloaded significantly more frequently, but found no evidence of a citation advantage for open access articles. The citation advantage from open access maight be caused by other factors. Results of the studies comparing the social media attention and citations/ downloads of the medical articles are often diametrically opposed.
Keywords: citation advantage; citation impact; citiranje; objave; odprti dostop; open access